Constructing Business-to-Business Marketing Models that Overcome the Limitations in Variable-Based and Case-Based Research Paradigms - Woodside, Arch (Best Business Books, 2015)
Purpose: This article describes the principal limitations frequently observable in variable-based and case-based research in business-to-business (B-to-B) marketing. Focus: The limitations relate to B-to-B theory construction, data collection, and data analysis and interpretation. The principal limitations in variable-based research include the reliance on regression (net effects) models in theory construction and the pervasive failure to test resulting empirical regression models for predictive validity. The principal limitations of case-based research are the frequent absence of rigorous theory formulation either pre- or postdata collection and failures to test propositions for predictive validity. Recommendations: The article directs attention to iconic studies that break free in part from these and additional limitations. The article offers useful steps on how to break free completely from the principal limitations. Managerial implications: B-to-B executives should insist that researchers include asymmetric algorithm models in reports that include symmetric (regression analysis) and analysis of variance findings.